Late Santonian-early Campanian lake-level fluctuations in the Songliao Basin, NE China and their relationship to coeval eustatic changes. (December 2018) - Yang, Daming; Huang, Yongjian; Guo, Wen; Huang, Qinghua; Ren, Yanguang; Wang, Chengshan
Abstract: In contrast to glacio-eustasy, which is mainly controlled by the waxing and waning of continental ice sheets during icehouse climate stages, the concept of aquifer or limno-eustasy suggests that the effects of groundwater storage and release may have been the main driver of short-term (10s kyr to a few Myr) sea-level changes in the Cretaceous ice-free world. Presumably climate-controlled hydrological cycling could change the water volumes of continental reservoirs and oceans by transporting water between continents and oceans, resulting in out-of-phase relation between lake and sea levels. In the present study, we present lake-level fluctuations in Members 1 and 2 of the Nenjiang Formation (late Santonian-early Campanian) in the Songliao Basin that are indicated by basin-scale correlations of Fischer Plots based on natural gamma-ray logging data. Meanwhile, the Al/K ratios of the SK1 core indicate that changes in precipitation forced lake-level fluctuations in the basin. Compared to global sea-level changes, lake-level fluctuations show an out-of-phase relation with sea-level variations in the lacustrine phase of the basin, suggesting that climate-driven water transport between continents and oceans controlled short-term sea-level changes in the late Santonian-early Campanian. During the phase of marine-lake connectivity (basal Nenjiang Member 1), although the marine regression-driven decrease in lake-level corresponds to salinity stratification and strongly reducing water conditions, increasing precipitation in the basin implies that the hydrological cycle transported more water from the oceans toward continents. Based on the results we suggest that limno-eustasy controlled water levels in the Songliao basin in the late Santonian-early Campanian. Highlights: The paper provides detailed lake-level fluctuations of Members 1 and 2 of the Nenjiang Formation in the Songliao Basin (late Santonian-early Campanian). Comparison of the lake and sea levels proves that limno-eustasy controlled water levels in the Songliao basin and possibility of different water conditions for the two oil shale intervals of Members 1 and 2.